The use of simulators in the learning for otologic surgery - de Sousa, Ana Maria Almeida; Okada, Daniel Mochida; Suzuki, Fabio Akira (Arquivos Internacionais de Otorrinolaringologia, 2011)
Introduction: The teaching method of “learn by doing it'' was created by Halsted e col. In the beginning of 20th century creating the first model of medical residence in the world. This learning develops in three phases: cognitive, associative and autonomous, through an ascending curve. The simulators appeared in the last years as a complement to the cognitive phase, adding efforts to the training, performed before only in animals and cadavers, ever more hampered by medical and legal dilemmas.Objective: Describe and compare the various types of simulators available for the learning of otological surgery.Data synthesis: The model of simulators are divided mainly in real and virtual models, each having its peculiarities with positive and negative points. The main point of each one of them is the sensory feedback granted by each one of them, what we call it haptic reality: coloring of the structure dissected; listening to the corresponding sounds; as the drill or vacuum; presence of a joystick that simulates the pen motor; use of glasses or even a microscope for three dimensional view; use of a real otologic surgical instrument. The cost of the differents types of simulators is also a key point for the implementation of them in the daily reality of the training centers. Is important to mention that some of these simulators allow the training students and can be objectively evaluated by the simulator itself.Conclusion: Simulators are seen as a complementary tool for training and improvement of the otological surgeons.
Keywords: teaching materials; anatomical models; otological surgical procedures; otolaryngology